Dual-supported photocatalyst as well as preparation method and application thereof
By supporting titanium dioxide and nickel phosphide active particles on the N-doped supercrosslinked polymer support, a dual-supported photocatalyst was prepared, which solved the problems of stability, durability and contact difficulties of existing photocatalysts, achieved efficient photocatalytic degradation and hydrogen production performance, and demonstrated excellent cycling stability.
Patent Information
- Application Number
- CN202411839104.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-11
AI Technical Summary
The existing photocatalysts have problems in stability, durability and alkaline solutions, making it difficult to effectively degrade plastic waste, and it is difficult to contact the catalytic center with the reaction substrate.
Using the preparation method of a dual-supported photocatalyst, the N-doped supercrosslinked polymer was prepared as a support through supercrosslinking reaction, and the active particles of titanium dioxide and nickel phosphide were supported on the support by oxidation heat treatment and phosphating treatment to form a dual-supported photocatalyst with a multi-stage pore structure.
It achieves efficient photocatalytic degradation and hydrogen production performance, has excellent cyclic stability and high specific degradation activity catalytic degradation TOF value, and can circulate catalytic degradation and hydrogen evolution under sunlight.
Smart Images

Figure CN119588419A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic degradation prepared by organic porous materials, and in particular to a double-loaded photocatalyst and a preparation method and application thereof. Background Art
[0002] In the rapidly developing modern world, the demand for petroleum-based raw materials has increased dramatically, leading to the depletion of energy and the surge in environmental problems. Therefore, a type of green energy that is expected to replace petroleum-based fuels has received widespread attention, such as hydrogen (H2), which is a non-carbon energy source. Its calorific value is more than twice that of traditional fuels such as gasoline, and it does not produce any toxic or harmful gases when used. However, the current conventional hydrogen production methods, such as hydrogen production from petroleum-based fuels and hydrogen production from water electrolysis, have high energy consumption in the process on the one hand, and require the use of a large amount of non-renewable energy such as petroleum-based on the other hand. Therefore, it is urgent to develop a new hydrogen production strategy such as photocatalytic water hydrogen production, using cheap and inexhaustible solar energy to replace traditional electricity and heat energy, etc., to form a sustainable green hydrogen production strategy. In addition, the difficulty in recycling and degrading plastic waste has caused serious environmental pollution problems, so it is urgent to develop effective plastic degradation photocatalysts to achieve simple, low-cost and efficient plastic recycling, thereby alleviating the increasingly serious environmental pressure.
[0003] At present, traditional photodegradation catalysts have many problems in terms of stability, durability, and the need to use a large amount of alkaline solutions. Therefore, it is urgent to develop more stable and more effective photocatalysts, promote the contact between the substrate and the catalytic active center, select suitable solvents, etc., to form a green and sustainable waste plastic recycling system. In particular, the screening of catalyst carrier skeletons not only needs to make up for the defects of homogeneous catalysts that are difficult to recycle, but also solve the problems of the difficulty of contact between the catalytic center and the reaction substrate in heterogeneous catalysis. Therefore, it is urgent to design a new porous carrier. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a dual-loaded photocatalyst and a preparation method and application thereof.
[0005] The objective of the present invention is achieved through the following technical solutions: <First aspect> The present invention provides a method for preparing a dual-loaded photocatalyst, comprising the following steps: S1, preparing N-doped hyper-crosslinked polymer as a carrier; S2, loading active particles of titanium dioxide and nickel phosphide on the carrier.
[0006] As an embodiment, in step S2, active particles of titanium dioxide and nickel phosphide are sequentially loaded on the carrier.
[0007] As an embodiment, the preparation method of the carrier is: mixing cyanuric chloride, carbazole and ferric chloride in a first solvent, stirring to react, extracting solid matter, and obtaining the carrier.
[0008] As an embodiment, the stirring reaction is carried out at 20-35 °C.
[0009] In some embodiments, the stirring reaction is carried out at room temperature.
[0010] As an embodiment, the molar ratio of cyanuric chloride to carbazole is (3-2):1.
[0011] In some embodiments, the mass ratio of cyanuric chloride to carbazole is 16:5.
[0012] As an embodiment, the amount of ferric chloride used is 60-70% of the mass of carbazole.
[0013] In some embodiments, the mass of the ferric chloride is 65% of that of the carbazole.
[0014] In some embodiments, the first solvent is chloroform.
[0015] As an embodiment, titanium dioxide and nickel phosphide are sequentially loaded on the support by an oxidative heat treatment method.
[0016] As an embodiment, the carrier, glacial acetic acid and butyl titanate are placed in a second solvent, and the reaction is fully stirred. The solid product is extracted and subjected to a first oxidation heat treatment to obtain a carrier loaded with titanium dioxide.
[0017] As an embodiment, the first oxidation heat treatment is carried out at a temperature of 700-900°C for 1.5-3 h.
[0018] In some embodiments, the first oxidation heat treatment is performed at a temperature of 800° C. for 2 h.
[0019] As an embodiment, the mass ratio of the carrier to glacial acetic acid and butyl titanate is (8~12): (45~55): 1.
[0020] In some embodiments, the mass ratio of the carrier to glacial acetic acid and butyl titanate is 10:50:1.
[0021] In some embodiments, the second solvent is N,N-dimethylformamide.
[0022] As an implementation scheme, nickel acetate, 1,3-propylene glycol and isopropanol are mixed to obtain a precursor solution, the titanium dioxide-loaded carrier is added, a second oxidation heat treatment is performed to obtain a Ti / Ni-loaded carrier, and then a phosphating treatment is performed to obtain the dual-loaded photocatalyst.
[0023] As an embodiment, the molar ratio of nickel acetate, 1,3-propylene glycol and isopropanol in the precursor solution is 1: (1.5~2.5): (1.5~2.5).
[0024] In some embodiments, the molar ratio of nickel acetate, 1,3-propylene glycol, and isopropanol in the precursor solution is 1:2:2.
[0025] As an embodiment, the dosage ratio of the titanium dioxide-loaded carrier to the precursor solution is 2-6 mg: 1 mL.
[0026] In some embodiments, the dosage ratio of the titanium dioxide-loaded carrier to the precursor solution is 5 mg: 1 mL.
[0027] As an embodiment, the second oxidation heat treatment is carried out at a temperature of 150-200°C and for a time of 10-15 h.
[0028] In some embodiments, the second oxidation heat treatment is performed at a temperature of 160° C. for 12 h.
[0029] As an embodiment, the phosphating method is: placing the Ti / Ni loaded carrier and red phosphorus separately, and performing atmosphere heat treatment, wherein the red phosphorus is placed above the carrier, and the temperature is raised to 450~550°C in a nitrogen atmosphere, maintained for 1.5~3 hours, and cooled to room temperature.
[0030] <Second Aspect> The invention provides a double-loaded photocatalyst, which is prepared by adopting the preparation method of the double-loaded photocatalyst.
[0031] A double-loaded photocatalyst comprises an N-doped hyper-crosslinked polymer skeleton and titanium dioxide and nickel phosphide active particles loaded on the skeleton.
[0032] As an embodiment, the dual-supported photocatalyst has a multi-level pore structure including micropores and mesopores.
[0033] As an embodiment, the dual-loaded photocatalyst contains 6-7 mmol / g of N element, 3.5-4.1 mmol / g of Ti element, and 4-4.5 mmol / g of Ni element.
[0034] <Third Aspect> The present invention provides application of the dual-loaded photocatalyst in degrading plastics.
[0035] In the application of dual-loaded photocatalysts in the degradation of plastics, the plastics are first pretreated in a KOH aqueous solution, and then the pretreated plastics and the dual-loaded photocatalysts are subjected to light treatment under a protective atmosphere for degradation.
[0036] As an embodiment, the protective atmosphere is one of nitrogen, argon and helium.
[0037] In some embodiments, the protective atmosphere is nitrogen.
[0038] As an embodiment, the light treatment uses one or more of a mercury lamp, an ultraviolet lamp, a xenon lamp, and an LED lamp.
[0039] In some embodiments, the light treatment uses a mercury lamp.
[0040] As an embodiment, during a single degradation, the mass ratio of the dual-loaded photocatalyst to the plastic to be degraded is 1: (5~15).
[0041] In some embodiments, during a single degradation, the mass ratio of the dual-loaded photocatalyst to the plastic to be degraded is 1:10.
[0042] As an embodiment, the dual-supported photocatalyst has a specific degradation activity for PET plastics and a catalytic degradation TOF value of 52h -1 .
[0043] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a preparation method of a dual-loaded photocatalyst, using a hypercrosslinking reaction to obtain a covalently bonded skeleton carrier with a large number of multi-level pore structures, and loading active particles of titanium dioxide and nickel phosphide on the carrier through two oxidation heat treatments, thereby obtaining a dual-loaded photocatalyst with the advantages of large specific surface area, rich N content, good thermal stability, and low density. The preparation method is simple, using FeCl3 as a catalyst, which is low in price, does not require heating at room temperature, reduces the preparation cost, and does not require the introduction of nitrogen. The prepared carrier has a lamellar structure, which greatly improves the substrate-catalytic center contact, and then the photocatalytic active particles are loaded by oxidation heat treatment and hydrothermal method to give the catalyst efficient photocatalytic degradation and hydrogen production performance and excellent cycle stability. Cyclic catalysis of PET / PLA degradation and hydrogen evolution under sunlight, and a degradation rate of more than 84.5% can still be maintained after eight cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 Schematic diagram of the preparation route of the dual-loaded photocatalyst in the present invention; Figure 2 This is a schematic diagram of the structure of the dual-loaded photocatalyst provided by the present invention; Figure 3 TEM image of the N-doped hyper-crosslinked polymer carrier prepared in Example 1 of the present invention; Figure 4 This is the infrared spectrum of the N-doped hyper-crosslinked polymer carrier prepared in Example 1 of the present invention; Figure 5 TEM image of the N-Ni2P-TiO2 catalyst prepared in Example 1 of the present invention; Figure 6 TEM image of the Ni2P / TiO2 catalyst without carrier prepared in Comparative Example 4 of the present invention; Figure 7 This is a comparison chart of the efficiency of various catalyst samples of the present invention in catalyzing plastic degradation; Figure 8 The hydrogen production efficiency diagram of each catalyst sample of the present invention in the first five days when used to catalyze plastic degradation; Fig. 9 This is a cyclic stability performance diagram of the N-Ni2P-TiO2 catalyst prepared in Example 1 of the present invention when used to catalyze the degradation of PET plastic. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0046] This specific embodiment provides a method for preparing a dual-loaded photocatalyst, such as Figure 1 As shown, the following steps are included: S1, preparing N-doped hyper-crosslinked polymer carrier; S2, loading active particles of nickel phosphide / titanium dioxide (Ni2P / TiO2) on a carrier.
[0047] The schematic diagram of the structure of the prepared dual-loaded photocatalyst is shown in Figure 2 shown.
[0048] The preparation method of the photocatalyst is specifically introduced below through examples.
[0049] Example 1 This embodiment provides a method for preparing a dual-loaded photocatalyst, the steps are as follows: In step S1, 6.4 g of cyanuric chloride and 2 g of carbazole were added to 200 mL of chloroform in sequence, and then 1.3 g of FeCl3 catalyst was added. The mixture was stirred for 12 h at room temperature. After the reaction was completed, the solvent was removed by filtration to obtain 5.01 g of a gray solid product, namely, N-doped hypercrosslinked polymer, which was used as a carrier for subsequent loading of photocatalytically active particles. The TEM micromorphology is shown in FIG. Figure 3 As shown, it presents a lamellar structure, which is conducive to the contact between the carrier and the active particles.
[0050] The infrared spectrum of the carrier sample is as follows Figure 4 As shown, it can be seen that 3350 cm -1 The absorption peaks on the left and right are NH vibration peaks, which originate from the carbazole part, while the absorption peaks at 1485 cm -1 and 1355 cm -1 The absorption peaks on the left and right represent C=N vibration peaks, which originate from the cyanuric chloride part.
[0051] The carrier sample was subjected to quantitative elemental detection and analysis using a CHN element analyzer Vario EL cube. The test results are listed in Table 1. The N content in the carrier was 7.34 mmol / g, indicating that the carrier had a rich N content and had a strong complexing effect on the metal particles, which was the key to enabling the subsequently introduced photocatalytic active particles (Ni2P / TiO2) to be evenly and stably distributed on the carrier.
[0052] The S2 step is divided into two steps: S21. Prepare TiO2 particles by an oxidative heat treatment method, and load them onto a carrier to obtain an N-doped hyper-crosslinked polymer carrier loaded with TiO2.
[0053] Specifically: using 20 mL of DMF as solvent, 0.5 g of glacial acetic acid, 10 mg of butyl titanate (TBOT) and 100 mg of the carrier were added to the solvent in sequence. After stirring at room temperature for 12 h, the solvent was removed and the solid product was dried at room temperature for 12 h, and then heated at 800 °C for 2 h to obtain an N-doped hyper-cross-linked polymer carrier loaded with TiO2 (hereinafter referred to as the intermediate carrier).
[0054] S22, loading Ni2P particles on the intermediate carrier.
[0055] Specifically, Ni(AC)2·H2O, 1,3-propylene glycol, and isopropanol in a molar ratio of 1:2:2 were prepared into a precursor solution of 10 mL, 100 mg of the intermediate carrier obtained in step S21 was added, and the mixture was kept at 160 °C for 12 h, followed by phosphating to obtain an N-doped hyper-crosslinked polymer-supported photocatalytically active particle nickel phosphide / titanium dioxide (Ni2P / TiO2) catalyst, hereinafter referred to as N-Ni2P-TiO2 catalyst. The TEM morphology image is shown in FIG. Figure 5 As shown, it can be seen that the active particles have good dispersibility, and the catalyst has a multi-level pore structure, including micropores within 2 nm and mesopores from 2 to 50 nm, and the active particles are loaded on the skeleton.
[0056] The phosphating treatment is as follows: the above sample and red phosphorus are placed in two quartz arks respectively. The red phosphorus is placed on the upper side of the tube furnace, and the sample is placed on the lower side of the ark containing the red phosphorus. The temperature is raised to 500°C at 5°C / min in a nitrogen atmosphere, maintained for 2 hours, and cooled to room temperature.
[0057] The N-Ni2P-TiO2 catalyst sample was quantitatively detected and analyzed using a CHN element analyzer Vario EL cube. The test results are listed in Table 1. The Ni element content was 4.31 mmol / g, the Ti element content was 3.92 mmol / g, the N element content was 6.09 mmol / g, and the C element content was 61.7 mmol / g, indicating that this method can successfully load the catalytically active particles nickel phosphide / titanium dioxide (Ni2P / TiO2) on the N-doped hyper-cross-linked polymer with a high content, which provides a guarantee for the subsequent catalytic plastic degradation and high efficiency of hydrogen production.
[0058] Comparative Example 1 In this comparative example, an N-doped hyper-crosslinked polymer was prepared by the same method as step S1 in Example 1, without performing the subsequent step S2.
[0059] A polymer free of active particles was prepared.
[0060] Comparative Example 2 The steps of this comparative example are basically the same as those in Example 1, except that: Prepare the N-doped hyper-crosslinked polymer carrier by step S1; TiO2 particles are loaded on the carrier through step S21.
[0061] Step S22 is not performed.
[0062] The N-doped super-crosslinked polymer loaded with TiO2 (hereinafter referred to as Ti-loaded polymer) was prepared.
[0063] Comparative Example 3 The steps of this comparative example are basically the same as those in Example 1, except that: Prepare the N-doped hyper-crosslinked polymer carrier by step S1; Step S21 is not performed; Ni2P particles are loaded on the carrier through the S22 step.
[0064] That is, Ni(AC)2·H2O, 1,3-propylene glycol, and isopropanol in a molar ratio of 1:2:2 are prepared as a precursor solution, 100 mg of the carrier obtained in step S21 is added, and the mixture is kept at 160°C for 12 h, followed by phosphating to obtain a Ni2P-loaded N-doped hyper-cross-linked polymer (hereinafter referred to as Ni-loaded polymer).
[0065] Comparative Example 4 The steps of this comparative example are basically the same as those in Example 1, except that: The preparation of the carrier in step S1 is not performed; Prepare unsupported TiO2 particles by step S21; The Ni2P particles loaded on the unsupported TiO2 particles are prepared by step S22.
[0066] That is, 20 mL of DMF was used as a solvent, 0.5 g of glacial acetic acid and 10 mg of butyl titanate were added to the solvent in sequence, and after stirring at room temperature for 12 h, the solvent was removed and the solid product was dried at room temperature for 12 h, and then heated at 800 ° C for 2 h to obtain TiO2 active particles; A precursor solution was prepared with Ni(AC)2·H2O, 1,3-propylene glycol and isopropanol in a molar ratio of 1:2:2, 100 mg of TiO2 active particles were added, and the solution was kept at 160 °C for 12 h, followed by phosphating to obtain a Ni2P / TiO2 catalyst without a carrier.
[0067] The TEM morphology image of the catalyst is shown in Figure 6 As shown, it can be seen that the active particles are seriously aggregated.
[0068] Table 1 Element contents in carriers and photocatalysts (unit: mmol / g)
[0069] This specific embodiment also provides the use of the above-mentioned N-Ni2P-TiO2 catalyst for degrading plastics.
[0070] Application of Catalyst (1) Degradable PET plastic 1 g of PET plastic was stirred in 20 mL of 10 M KOH aqueous solution for 12 h for pretreatment; The pretreated plastic and 100 mg of catalyst were placed in a quartz tube. The atmosphere in the quartz tube was replaced with nitrogen. The tube was then sealed after being pressurized to 1 MPa and placed in a photochemical instrument connected to a mercury lamp (500 W). The tube was treated with light and the hydrogen production rate was detected by gas chromatograph (GC-TCD). The composition and structure of the residual plastic after catalysis were analyzed using a nuclear magnetic resonance spectrometer (NMR) to obtain the efficiency of photocatalytic degradation.
[0071] After the degradation was completed, the catalyst was extracted and a new round of PET plastic degradation was carried out again. It was reused 8 times in total to test the catalyst's cyclic application stability.
[0072] (2) Degradable PLA plastic The steps for degrading PET plastic are the same. The only difference is that PET plastic is replaced by PLA plastic, and other parameters are the same.
[0073] The degradation results of each embodiment and comparative example are listed in Figures 7 to 9 It can be seen that the degradation rates of the catalysts prepared in Comparative Examples 1, 2 and 3 are the lowest. Although the catalyst without a carrier in Comparative Example 4 contains catalytically active particles and has relatively high catalytic activity, the lack of a carrier leads to serious agglomeration of active particles, thus exposing fewer active centers and having much lower catalytic activity than Example 1. The N-Ni2P-TiO2 catalyst prepared in Example 1 has high catalytic activity, with first-round degradation rates of PET and PLA reaching about 86.1% and 98%, respectively. After repeated cycle tests, the degradation rate of PET remained above 84.8% after the eighth round of degradation. This indicates that the N-Ni2P-TiO2 catalyst has excellent cyclic stability. The TOF value of the catalyst for catalytic degradation of PET plastic is 52h -1 ( ).
[0074] In the first five days of the degradation test, the hydrogen production rate was analyzed, and it was found that the hydrogen production rate of the catalysts prepared in Comparative Examples 1 to 3 was always low, and the hydrogen production rate of the catalyst prepared in Comparative Example 4 gradually increased to 50 μmol H2gsub -1 The catalyst of Example 1 is about 20 μmolH2gsub -1 Increased to about 89.8 (PET) or about 101.8 (PLA) μmol H2gsub -1 . Further, if Fig. 9 As shown, the catalyst of Example 1 has a maximum hydrogen production rate of 100.5 μmolH2gsub in the first round of PET degradation. -1In the eighth round of degradation, the hydrogen production rate remained at 91.4 μmolH2gsub -1 It can be seen that the hydrogen production rate of N-Ni2P-TiO2 catalyst in the degradation process of PET and PLA is at a high level, and tends to be stable on the fifth day. It still has a high catalytic ability after eight cycles.
[0075] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a dual-loaded photocatalyst, characterized in that: The following steps are involved: S1, preparing N-doped hyper-crosslinked polymer as a carrier; S2, loading active particles of titanium dioxide and nickel phosphide on the carrier in sequence; wherein cyanuric chloride, carbazole and ferric chloride are mixed in a first solvent, stirred for reaction, and solid matter is extracted to obtain the carrier; The carrier, glacial acetic acid and butyl titanate are placed in a second solvent, and the mixture is stirred sufficiently for reaction, and a solid product is extracted for a first oxidation heat treatment to obtain a carrier loaded with titanium dioxide; Nickel acetate, 1,3-propylene glycol and isopropanol are mixed to obtain a precursor solution, the carrier loaded with titanium dioxide is added, a second oxidation heat treatment is performed, and then a phosphating treatment is performed to obtain the dual-loaded photocatalyst.
2. The method for preparing a dual-supported photocatalyst according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The molar ratio of cyanuric chloride to carbazole is (3-2): 1; B. The amount of ferric chloride used is 60-70% of the mass of carbazole; C. The mass ratio of the carrier to glacial acetic acid and butyl titanate is (8-12): (45-55): 1; D. The molar ratio of nickel acetate, 1,3-propylene glycol and isopropanol in the precursor solution is 1: (1.5-2.5): (1.5-2.5); E. The dosage ratio of the titanium dioxide-loaded carrier to the precursor solution is 2-6 mg: 1 mL.
3. The method for preparing a dual-supported photocatalyst according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The first oxidation heat treatment is performed at a temperature of 700-900°C for 1.5-3 hours; B. The second oxidation heat treatment is carried out at a temperature of 150-200°C and a time of 10-15 h.
4. A dual-loaded photocatalyst, characterized in that: The photocatalyst is prepared according to the preparation method of the dual-loaded photocatalyst according to any one of claims 1 to 3.
5. The dual-supported photocatalyst according to claim 4, characterized in that: The catalyst comprises an N-doped hyper-crosslinked polymer skeleton and titanium dioxide and nickel phosphide active particles loaded on the skeleton.
6. The dual-supported photocatalyst according to claim 4, characterized in that: The dual-loaded photocatalyst has a multi-level pore structure including micropores and mesopores.
7. The dual-supported photocatalyst according to claim 4, characterized in that: The double-loaded photocatalyst contains 6-7 mmol / g of N element, 3.5-4.1 mmol / g of Ti element, and 4-4.5 mmol / g of Ni element.
8. The use of the dual-supported photocatalyst according to any one of claims 4 to 7, characterized in that: The catalyst is used to degrade plastics.
9. The use of the dual-supported photocatalyst according to claim 8, characterized in that: The plastic is first pretreated in an alkaline aqueous solution, and then the pretreated plastic and the photocatalyst are subjected to light treatment under a protective atmosphere for degradation.
10. The use of the dual-supported photocatalyst according to claim 9, characterized in that: Include one or more of the following technical features: A. During single degradation, the mass ratio of the photocatalyst to the plastic to be degraded is 1: (5-15); B. The TOF value of the photocatalyst for the catalytic degradation of PET plastic is 52h -1 .